Integrasi Sabar-Syukur dan Filosofi Stoikisme dalam Konstruksi Resiliensi Spiritual: Analisis Komparatif bagi Pengembangan Kurikulum Pendidikan Agama Islam di Era Disrupsi - Mahfud Mahfud; Solchan Ghozali (UPT Publikasi Ilmiah, 2026)
This research explores the integration of Sufistic psychology and Stoicism as a solution to the lack of spiritual resilience among students in the era of disruption. The research gap indicates that current Islamic Education (PAI) curricula often overemphasize ritual-cognitive aspects, failing to equip students with practical coping mechanisms against global pressures. The study aims to formulate a new resilience model through a comparative analysis of the convergences and divergences between the concepts of patience–gratitude and Stoic philosophy. This study employs a library research method with content analysis techniques on primary texts by Al-Ghazali, Al-Mawardi, Marcus Aurelius, and Epictetus. Data were collected through a documentation study of reputable journal articles published between 2021 and 2026. The main findings formulate the “Active-Patience” model, which synthesizes Islamic theocentric depth with the Stoic cognitive technique of the “Dichotomy of Control.” The theoretical contribution of this research lies in enriching the concept of interdisciplinary spiritual resilience. In conclusion, this integration effectively enhances students’ inner peace (thuma'ninah) and moral agency. Practical recommendations are directed at PAI curriculum developers to adopt Stoic–Sufistic reflection methods. Theoretical implications expand the boundaries of dialogue between revelation and reason, while practical implications offer character-based mental health instruments. Future research opportunities lie in the empirical testing of the Active-Patience model through classroom action research.